Identification of new potential allergens from Nile perch (Lates niloticus) and Cod (Gadus morhua) - Tomm, Janina; van Do, T.; Jende, Claudia; Simon, J.C.; Treudler, R.; von Bergen, Martin; Averbeck, M. (ESMON Publicidad, Barcelona, 2013)
Background: Globalization of the food industry has led to widespread exposure to new nondomestic fish species; therefore, identification of potential allergens is necessary in order to diagnose allergic reactions.Objective: Contact with a patient who was allergic to Nile perch (Lates niloticus) prompted us to investigate the immunoglobulin (Ig) E–reactive proteins that could be allergens of this species.Methods: 2D gel electrophoresis was used to separate the muscle proteins of L niloticus and Gadus morhua. Immunoblotting was performed with sera from 12 patients with a history of immediate-type allergic reaction to fish and from atopic and nonatopic controls. IgE-reactive proteins were detected and identified using mass spectrometry.Results: The index patient had low levels of IgE binding to parvalbumins. However, 8 putative allergens other than parvalbumin from L niloticus and 5 from G morhua were identified. Further investigation revealed cross-sensitivity to enolase 3 from L niloticus in 7 of the 12 fish-allergic individuals (58%), whereas 11 of the 12 patients (92%) were sensitized to enolase 3 from G morhua. However, atopic control patients were also sensitized to enolase 3 from L niloticus and G morhua.Conclusion: Identification of species-specific allergens and individual sensitization could help us to improve avoidance strategies.